Food as a lifestyle - M. V. Mayevskaya; R. M. Mayevsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of the clinical case presentation. To discuss the principles of the correct and healthy nutrition, which are the universal and applicable for the most of overweight and obese patients and obesity-related disorders, exemplified by clinical case. Summary. Obesity has multifactorial adverse effect on human body i.e.: predisposition to diabetes mellitus, cardiovascular diseases, excessive musculoskeletal load, cosmetic defect, etc. It represents serious problem for the majority of economically developed European countries, USA and Russia. Presented principles will help healthy people to maintain active longevity by prevention of cardio-vascular diseases, Alzheimer's disease and some other disorders. The data is presented in the form of a clinical discussion in which on the example of the young patient with morbid obesity all aspects of effective medical communication are analyzed in detail. Specific recommendations which the patient has to receive from the doctor are discussed: motivations for lifestyle modification, optimum daily caloric food load, amount of physical activity, optimum nutritional pattern.